If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+16=x+16
We move all terms to the left:
4x+16-(x+16)=0
We get rid of parentheses
4x-x-16+16=0
We add all the numbers together, and all the variables
3x=0
x=0/3
x=0
| 3x^2=100x+10000 | | 2(4x+5)+8=9+4(3x+1) | | 8/5+3x+7/10=-1 | | x+22=10 | | 8x+66=-2x-24 | | 2x-24=-5x+32 | | 7x+13=-3x+3 | | 1-(y-2)=5+y | | -3x-24=-9x-66 | | -3x+21=2x-24 | | 3x-17=-3x+19 | | 7x+31=-2x-14 | | 10x+74=7x+53 | | (3x-40)=(2x+20) | | 8m+4=4m+12 | | 25+10x-x^=7 | | 3y–12=52+y | | 8x+21=-10x-15 | | -7x-39=-4 | | 3x-15=-5x+9 | | .15y+y=7000 | | 2x+16=5x+28 | | 2(2(x+2)+x)=154 | | 2n+5=3n-10 | | 2(x)+3(x+1)+4(x+2)=56 | | 5/9x=13/6 | | 10x+75=-5x-45 | | 6x-16=-79 | | 4x-32=-3x+31 | | 8x+42=-51 | | -x-9=-10x-27 | | (47)−3×(1649)−1=(47)n−1 |